Identification of chemosensory receptor genes in Manduca sexta and knockdown by RNA interference - Howlett Natalie (BMC Genomics, 2012)
Abstract Background Insects detect environmental chemicals via a large and rapidly evolving family of chemosensory receptor proteins. Although our understanding of the molecular genetic basis for Drosophila chemoreception has increased enormously in the last decade, similar understanding in other insects remains limited. The tobacco hornworm, Manduca sexta, has long been an important model for insect chemosensation, particularly from ecological, behavioral, and physiological standpoints. It is also a major agricultural pest on solanaceous crops. However, little sequence information and lack of genetic tools has prevented molecular genetic analysis in this species. The ability to connect molecular genetic mechanisms, including potential lineage-specific changes in chemosensory genes, to ecologically relevant behaviors and specializations in M. sexta would be greatly beneficial. Results Here, we sequenced transcriptomes from adult and larval chemosensory tissues and identified chemosensory genes based on sequence homology. We also used dsRNA feeding as a method to induce RNA interference in larval chemosensory tissues. Conclusions We report identification of new chemosensory receptor genes including 17 novel odorant receptors and one novel gustatory receptor. Further, we demonstrate that systemic RNA interference can be used in larval olfactory neurons to reduce expression of chemosensory receptor transcripts. Together, our results further the development of M. sexta as a model for functional analysis of insect chemosensation.